THE EFFECT OF QUALITY SERVICE DIMENSIONS ON CUSTOMER SATISFACTION PT. APJ - Eri Marlapa Marlapa (Universitas Mercu Buana, 2020)
PENGARUH DIMENSI KUALITAS PELAYANAN JASA TERHADAP KEPUASAN PELANGGAN PT. APJOleh :Eri MarlapaFakultas Ekonomi Universitas Mercu Buana Jakartaeri.marlapa@mercubuana.ac.id ABSTRACTThis study analyzes the influence of the dimensions of service quality on customer satisfaction. PT. APJ. This study aims to describe the quality of services provided by PT. APJ and measuring performance are influenced by job satisfaction which directly impacts high productivity on customer satisfaction at PT. APJ is based on the Servqual (Service Quality) model. This research is a category of business research that uses quantitative descriptive research methods. The population in this study were staff of company contractor employees who were customers of PT. APJ. The number of samples is 25 customers, using the nonprobability sampling method. The type of sample chosen using purposive sampling technique. Data collection is done through a questionnaire. The analysis technique used is multiple regression. Based on the results of the analysis it was found that the dimensions of service quality which included physical evidence, reliability, responsiveness, assurance, empathy had a positive and significant effect on customer satisfaction.Keywords: Service Quality, Servqual Model, physical evidence, reliability, responsiveness, assurance, empathy, customer satisfaction